Two Unsaturated Fatty Acids with Potent alpha-Glucosidase Inhibitory Activity Purified from the Body Wall of Sea Cucumber (Stichopus japonicus) - The Han Nguyen; Um, Byung Hun; Kim, Sang Moo (WILEY, 2011)
One therapeutic approach for preventing diabetes mellitus and obesity is to retard the absorption of glucose via inhibition of a-glucosidase. Two unsaturated fatty acids with strong a-glucosidase inhibitory activity, 7(Z)-octadecenoic acid (1) and 7(Z),10(Z)-octadecadienoic acid (2), were purified from the body wall of Stichopus japonicus. IC50 values of compounds 1 and 2 were 0.51 and 0.67 mu g/mL against Saccharomyces cerevisiae a-glucosidase and 0.49 and 0.60 mu g/mL against Bacillus stearothermophilus a-glucosidase, respectively. These compounds mildly inhibited rat-intestinal sucrase and maltase. In addition, both compounds showed a mixed type of inhibition against S. cerevisiae a-glucosidase and were very stable under thermal and acidic conditions up to 60 min. The KI and KIS values of compounds 1 and 2 were 0.44 and 0.22 mu g/mL, and 0.39 and 0.13 mu g/mL, respectively.
Keywords: BOVINE SERUM-ALBUMIN; MUSHROOM TYROSINASE; ENZYME; MECHANISM; SAPONIN; BINDING